580 Psychosocial Functioning Mediates Parental Depression and Sleep Behaviors in Children with Autism Spectrum Disorder. (3rd May 2021) - Hayse, Braden; Stearns, Melanie; Nair, Neetu; Mazurek, Micah; Takahashi, Nicole; Muckerman, Julie; McCrae, Christina S
Abstract: Introduction: Parents who have been diagnosed with depression often report that their children have poor sleep behaviors. This relationship may occur because the children of parents with depression are more likely experience poor psychosocial functioning, which can negatively impact their sleep. Children with Autism Spectrum Disorder (ASD) are particularly at risk for sleep difficulties, and it is important to better understand these relationships as scant to no research has been done which investigates parental depression, child psychosocial functioning, and child sleep among children with ASD. The current study examined whether parental perception of their child's psychosocial functioning mediated the relationship between parental depression and their child's sleep behaviors. Methods: The sample (N=36) consisted of parents (81% female) reporting on their children aged 6–12 (M=8.56, SD = 1.86; 75% male). All children were diagnosed with ASD and had sleep complaints as reported by their parents. Children and their parents were recruited because they expressed interest in a behavioral treatment sleep study and these data come from the baseline data collection associated with that study. Measures included Sleep Behaviors factor from the Child Sleep Health Questionnaire (CSHQ), the Pediatric Symptom Checklist (PSC), and a question asking if the parent had been diagnosed with depression. Results: Analyses were conducting using AMOS 27.0. Child psychosocial functioning significantly mediated (β = .12) the relation between parental depression and child sleep behavior. Parents who had been diagnosed with depression were more likely to report greater child psychosocial difficulties (β =.39, p = .01) and child psychosocial difficulties were associated with a greater likelihood of the child having worse sleep behavior (β =.32, p = .04). The direct effect between parental depression and child sleep behavior was not significant. Conclusion: These results indicate that child psychosocial functioning may help to explain the connection between diagnosed parental depression and poor child sleep behavior among children with ASD. This suggests that psychosocial functioning may be an important aspect to target in sleep interventions, particularly for children with ASD. Support (if any): University of Missouri Research Board Grant (McCrae, PI); United States Department of Defense USAMRAA Autism Research Program (McCrae, PI; CTA AR190047).